Alfred Rolfe: forgotten pioneer Australian film director. Issue 2 (3rd May 2016) - Vagg, Stephen; Reynaud, Daniel
ABSTRACT: Alfred Rolfe was arguably the most prolific silent era Australian director. He was responsible for more than 25 feature films, encompassing the bushranger genres, early Australian war cinema and various melodramas. Many of his films were both critical and commercial successes. The only surviving footage is scenes from two of his 1915 war films. This important director has been overshadowed by his contemporaries, particularly Raymond Longford. This paper argues that Rolfe's contribution to early Australian cinema was significant, not just in volume, but also in artistic terms, in subject matter, and in popular appeal. The centenary of Anzac is also the centenary of Australia's first Gallipoli movie, Rolfe's The Hero of the Dardanelles (1915), which was one of the most successful films at the box office for its time.